Pelatihan Pengenalan Pemrograman Komputer pada SMA Dharma Bakti Lubuk Pakam - Arwin Halim; Hernawati Gohzali; Irpan Adiputra Pardosi; Ng Poi Wong; Sunario Megawan (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
The lack of ability of the students of SMA Dharma Bakti Lubuk Pakam in mastering computers, especially the programming field, is a significant challenge in preparing them for the digital era. In the industrial era 4.0, mastering programming skills is essential, especially the Python programming language which is widely used in data analysis, artificial intelligence, and application development. To overcome this problem, Mikroskil University organized an introduction to Python programming training through Community Service activities. The training covered both theory and hands-on practice to build a better understanding. To measure the success of the training, the pre-test and post-test were conducted as well as a quiz-based evaluation. The training results showed a significant increase in students' understanding level of 85.42%. The results of the evaluation of the level of mastery of the training material showed that 26.67% of students mastered the material well, and 16.66% of students moderately mastered the material. However, 56.67% of the students still lacked mastery of the material due to the limited duration of the training and limited experience in programming. Overall, this training succeeded in improving digital literacy for students while supporting technological transformation in the school environment. To improve the effectiveness of the training, a longer training duration and more interactive learning methods are recommended. It is also recommended that similar training be extended to other schools to improve the programming skills of the younger generation and their readiness to face the challenges of the digital industry.